Secondary battery and electric device

By designing a layered negative electrode film layer in the negative electrode sheet of the secondary battery, combining the second negative electrode active material with a high capacity and the first negative electrode active material of the carbon-clad layer, the challenges of existing secondary batteries in terms of kinetic performance and energy density are solved, and higher energy density and kinetic performance are achieved.

CN119852479AActive Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411301523.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-04-18
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

Existing secondary batteries have challenges in improving kinetic performance and energy density, especially in maintaining good kinetic performance while increasing energy density.

Method used

By designing a secondary battery including a negative electrode sheet, the negative electrode sheet consists of a negative electrode current collector, a negative electrode film layer and a negative electrode active material. The negative electrode film layer is divided into two areas. The first area contains the first negative electrode active material of a carbon coated layer, and the second area contains the second negative electrode active material with a high capacity.

Benefits of technology

The secondary battery maintains good dynamic performance while taking into account high energy density, improving the fast charging and cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852479A_ABST
    Figure CN119852479A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and a power utilization device. The secondary battery comprises a negative electrode piece, the negative electrode piece comprises a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer is provided with a first surface away from the negative electrode current collector and a second surface opposite to the first surface, and the thickness of the negative electrode film layer is marked as H, the area from the first surface of the negative electrode film layer to the thickness range of 0.3 H is marked as the first area of the negative electrode film layer, the area from the second surface of the negative electrode film layer to the thickness range of 0.3 H is marked as the second area of the negative electrode film layer, the first area comprises a first negative electrode active material, and the second area comprises a second negative electrode active material; the first negative electrode active material comprises a substrate and a carbon coating layer formed on at least part of the surface of the substrate; the lithium insertion platform voltage of the first negative electrode active material is 0.118-0.140 V, and the gram volume of the second negative electrode active material is greater than that of the first negative electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a secondary battery and an electrical device. Background Art

[0002] In recent years, as the application scope of secondary batteries becomes wider and wider, secondary batteries are widely used in energy storage power supply systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, aerospace and other fields. As secondary batteries have made great progress, higher requirements have been put forward for their dynamic performance and energy density. Summary of the invention

[0003] The present application is made in view of the above problems, and its purpose is to provide a secondary battery and an electric device. The secondary battery has high energy density while maintaining good dynamic performance.

[0004] In order to achieve the above-mentioned object, the present application provides a secondary battery, including a negative electrode plate, the negative electrode plate including a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer having a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, the thickness of the negative electrode film layer is recorded as H, the area within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the first area of ​​the negative electrode film layer, the area within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the second area of ​​the negative electrode film layer, the first area includes a first negative electrode active material, and the second area includes a second negative electrode active material. The first negative electrode active material includes a substrate and a carbon coating layer formed on at least part of the surface of the substrate; and the lithium insertion platform voltage of the first negative electrode active material is 0.118V to 0.140V, wherein the lithium insertion platform voltage is a charge and discharge test of a button cell prepared for the test material under the conditions of a lithium removal rate of 0.1C and a lithium insertion rate of 0.05C, respectively, to obtain a charge and discharge curve within the range of 0.005V-2.0V, wherein the ratio of the total lithium insertion energy within 0.005V-2.0V to the total lithium insertion capacity is defined as the lithium insertion platform voltage of the tested material; the gram capacity of the second negative electrode active material is greater than the gram capacity of the first negative electrode active material. Thus, the secondary battery has good kinetic performance while taking into account high energy density.

[0005] In some embodiments, the lithium insertion platform voltage of the first negative electrode active material is 0.123 V to 0.135 V. This is beneficial to further improve the kinetic performance of the secondary battery.

[0006] In some embodiments, the carbon coating layer includes soft carbon, which is beneficial for providing more active ion channels, thereby improving the kinetic performance of the secondary battery.

[0007] In some embodiments, the first negative electrode active material includes primary graphite particles and secondary graphite particles. By mixing the primary graphite particles and the secondary graphite particles, the dynamic performance of the secondary battery can be further improved.

[0008] In some embodiments, the amount of the secondary particle graphite material in the first negative electrode active material is greater than or equal to 60%. By using secondary particles as the main component in the first negative electrode active material, the isotropy is high, so that the expansion of the secondary battery during the cycle can be dispersed in all directions, reducing the expansion of the pole piece and improving the cycle performance.

[0009] In some embodiments, the OI value of the first negative electrode active material powder is 2.0 to 6.0. Thus, lithium ions can be embedded from all directions, improving the fast charging performance of the secondary battery.

[0010] In some embodiments, the gram capacity of the second negative electrode active material is greater than 359 mAh / g, thereby facilitating the improvement of the energy density of the secondary battery.

[0011] In some embodiments, the gram capacity of the second negative electrode active material is 360 mAh / g to 366 mAh / g, which is beneficial to improve the energy density of the secondary battery.

[0012] In some embodiments, the powder compaction density of the first negative electrode active material under a pressure of 50000N is 1.74g / cc to 1.79g / cc. As a result, it is beneficial to provide appropriate porosity in the first region, which is beneficial to the infiltration of the electrolyte. In some embodiments, the powder compaction density of the second negative electrode active material under a pressure of 50000N is 1.95g / cc to 2.04g / cc. As a result, it is beneficial to provide appropriate porosity in the second region and to improve the energy density of the secondary battery. In some embodiments, the volume distribution particle size Dv50 of the first negative electrode active material is 7.8μm to 15.8μm. By making the volume distribution particle size Dv50 of the first negative electrode active material in the above range, it is beneficial to form a better pore distribution state in the first region of the pole piece, which is more beneficial to improve the transmission performance of ions and electrons and improve the fast charging performance of the battery.

[0013] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the first negative electrode active material is 0.90 to 1.50. The particle size distribution within this range indicates that the negative electrode active material particles are well distributed, which is conducive to the upper region of the negative electrode film layer having a suitable pore structure, thereby reducing the difficulty of ion liquid phase transmission and further improving the kinetic performance of the secondary battery.

[0014] In some embodiments, the BET specific surface area of ​​the first negative electrode active material is 0.6 m 2 / g to 1.3m 2 This is beneficial to reducing the side reaction activity on the surface of the first negative electrode active material and improving the cycle performance of the secondary battery.

[0015] In some embodiments, the gram capacity of the first negative electrode active material is 350.5 mAh / g to 358.5 mAh / g, which is beneficial to improve the energy density of the secondary battery.

[0016] In some embodiments, the La(110) of the second negative electrode active material is 130nm-175nm, and the Lc(002) is 30nm-42nm, wherein La(110) represents the crystallite size along the a-axis in the (110) crystal plane of the material, and Lc(002) represents the crystallite size along the c-axis in the (002) crystal plane of the material. Thus, the secondary battery has a high energy density.

[0017] In some embodiments, La(110) / Lc(002) is 3.5 to 5.5, which is beneficial for the secondary battery to have a high energy density.

[0018] In some embodiments, a charge and discharge test is performed on a button cell prepared from the second negative electrode active material under the conditions of a lithium removal rate of 0.1C and a lithium insertion rate of 0.05C, respectively, to obtain a charge and discharge curve in the range of 0.005V to 2.0V. In the discharge curve of the second negative electrode active material, a lithium insertion platform exists in the voltage range of 0.005V to 0.070V, and the discharge capacity corresponding to the lithium insertion platform accounts for more than 43% of the total discharge capacity of the button cell. This is conducive to improving the energy density of the secondary battery.

[0019] In some embodiments, the ratio X1 of the discharge capacity corresponding to the lithium embedded platform to the total discharge capacity of the button cell is 43% to 47%.

[0020] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the second negative electrode active material is 0.9 to 1.25, which is beneficial to improve the active ion and electron transport performance in the negative electrode film layer, thereby improving the kinetic performance of the secondary battery.

[0021] In some embodiments, the BET specific surface area of ​​the second negative electrode active material is 0.8 m 2 / g~2.1m 2 / g. This is beneficial to reducing the side reaction activity on the surface of the negative electrode active material, thereby improving the cycle performance and the first coulombic efficiency of the secondary battery.

[0022] In some embodiments, the mass ratio of the first negative electrode active material to the second negative electrode active material is 4:6 to 6:4. This is beneficial for improving the kinetic performance of the secondary battery while taking into account the energy density.

[0023] In some embodiments, the compaction density of the negative electrode film layer is 1.50 g / cc to 1.90 g / cc, which is beneficial for the negative electrode film layer to have both high capacity and good active ion and electron transport properties, and thus for the secondary battery to have both high energy density and good kinetic performance.

[0024] In some embodiments, the surface density of the negative electrode film layer is 6.0 mg / cm 2 ~24.0mg / cm 2 This is beneficial for the negative electrode film layer to have both high capacity and good active ion and electron transport performance, and further beneficial for the secondary battery to have both high energy density and good kinetic performance.

[0025] In some embodiments, the thickness of the negative electrode film layer is 60 μm-240 μm, which is beneficial for the secondary battery to have good dynamic performance while taking into account energy density.

[0026] In some embodiments, the porosity of the first region is greater than the porosity of the second region. By setting the negative electrode film layer as a double layer, wherein the porosity of the upper region (the first region) is greater than the porosity of the lower region (the second region), the contact opportunity between the first region and the active ions in the electrolyte is increased, so that the active ions can migrate faster during the charge and discharge process, improving the lithium insertion kinetics of the material, thereby improving the kinetic performance of the battery.

[0027] In some embodiments, the method for preparing the first negative electrode active material comprises:

[0028] Providing a base material;

[0029] After mixing the base material and the organic carbon source, heat treatment is performed to obtain the first negative electrode active material;

[0030] Wherein, the mass ratio of the matrix material to the organic carbon source is 100:1.5 to 100:8.

[0031] Thus, by setting the matrix material and the organic carbon source within the above mass ratio range, the lithium insertion platform voltage of the obtained first negative electrode active material is made to be 0.118V to 0.140V.

[0032] The second aspect of the present application provides an electric device, comprising the secondary battery of the first aspect of the present application. Since the electric device of the present application comprises the secondary battery provided by the present application, it has at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic diagram of an embodiment of the negative electrode plate of the present application.

[0034] Figure 2 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0035] Figure 3 Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.

[0036] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.

[0037] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0038] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0039] Figure 7 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0040] Figure 8 The charge and discharge curves are obtained by charging and discharging button cells prepared from material 1-1 and material 1-6.

[0041] Fig. 9 This is the charge and discharge curve obtained by charging and discharging the button battery prepared with material 2-1.

[0042] Fig.10 This is an image obtained by scanning material 1-1 using a transmission electron microscope (TEM).

[0043] Fig.11 This is an image obtained by scanning the negative electrode sheet prepared in Example 1 of the present application using a scanning electron microscope (SEM).

[0044] Description of reference numerals:

[0045] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly; 10 negative electrode plate; 101 negative electrode current collector; 102 negative electrode film layer; 102a first surface; 102b second surface; 1021 first area; 1022 second area; 1023 middle area. DETAILED DESCRIPTION

[0046] Hereinafter, the embodiments of the secondary battery and the electric device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0047] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0048] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0049] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0050] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.

[0051] If not otherwise specified, the values ​​of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.

[0052] If not otherwise specified, in the present application, the term "active ions" refers to ions that can be intercalated and extracted back and forth between the positive electrode and the negative electrode of a secondary battery, including but not limited to lithium ions.

[0053] At present, in order to improve the energy density of secondary batteries, the negative electrode plates are usually thickly coated to prepare high-load electrodes. Although the thick coating design improves the energy density of the battery cell by increasing the total amount of active materials, the increase in thickness will lead to an increase in the charge migration path and limited electron and active ion transmission kinetics, resulting in the deterioration of the kinetic performance of the secondary battery, such as fast charging performance.

[0054] Based on this, the present application proposes a secondary battery and an electrical device. The secondary battery has improved dynamic performance and high energy density. The present invention and optional implementation methods are described in more detail below.

[0055] Secondary battery

[0056] The present application provides a secondary battery. The term "secondary battery" mentioned herein refers to a battery cell, a battery module or a battery pack. Each of the above is described below.

[0057] A secondary battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0058] Negative electrode

[0059] The secondary battery of the present application comprises a negative electrode plate, the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer has a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, the thickness of the negative electrode film layer is recorded as H, the region within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the first region of the negative electrode film layer, the region within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the second region of the negative electrode film layer, the first region comprises a first negative electrode active material, the second region comprises a second negative electrode active material, the first negative electrode active material comprises a substrate and a substrate formed on the substrate a carbon coating layer on at least a portion of the surface of the body; and the lithium insertion platform voltage of the first negative electrode active material is 0.118V to 0.140V, wherein the lithium insertion platform voltage is a charge and discharge test of a button cell prepared for the test material under the conditions of a lithium desorption rate of 0.1C and a lithium insertion rate of 0.05C, respectively, to obtain a charge and discharge curve in the range of 0.005V-2.0V, wherein the ratio of the total lithium insertion energy in the range of 0.005V-2.0V to the total lithium insertion capacity in the range of 0.005V-2.0V is defined as the lithium insertion platform voltage of the tested material; the gram capacity of the second negative electrode active material is greater than the gram capacity of the first negative electrode active material.

[0060] In the present application, by setting the first negative electrode active material in the upper layer (first region) to include a carbon coating layer, on the one hand, due to its good conductivity and ion transmission ability, it can provide more ion transmission channels on the surface of the substrate, thereby increasing the lithium insertion channel, and on the other hand, the carbon coating layer reduces the surface area of ​​the substrate, effectively reducing the co-intercalation phenomenon of the electrolyte, thereby reducing the interface impedance, but the presence of the carbon coating layer will also have a certain effect on the gram capacity of the material. Lithium insertion channels and interface impedance are important factors affecting the lithium ion transmission speed and efficiency, and thus affect the lithium insertion platform voltage. In the present application, by making the first negative electrode active material have a lithium insertion platform voltage of 0.118V to 0.140V (greater than 0.118V), it means that the material can quickly deintercalate the active ions on the surface of the first negative electrode active material while maintaining a high gram capacity, and it is less likely to precipitate lithium, thereby effectively improving the kinetic performance of the secondary battery. At the same time, further, by setting the gram capacity of the second negative electrode active material in the lower layer (second region) to be greater than the gram capacity of the first negative electrode active material, the secondary battery has a high energy density.

[0061] See also Figure 1 , which shows a schematic diagram of an embodiment of the negative electrode sheet of the present application. Figure 1As shown, the negative electrode sheet 10 includes a negative electrode current collector 101 and a negative electrode film layer 102 formed on at least one surface of the negative electrode current collector 101. The negative electrode film layer 102 has a first surface 102a away from the negative electrode current collector 101 and a second surface 102b arranged opposite to the first surface 102a. The thickness of the negative electrode film layer 102 is recorded as H. The thickness H of the negative electrode film layer refers to the thickness of the negative electrode film layer located on one side of the negative electrode current collector. The area within the range of 0.3H thickness from the first surface 102a of the negative electrode film layer is recorded as the first area 1021 (upper layer) of the negative electrode film layer. The area within the range of 0.3H thickness from the second surface 102b of the negative electrode film layer is recorded as the second area 1022 (lower layer) of the negative electrode film layer. The first area 1021 includes a first negative electrode active material, and the second area 1022 includes a second negative electrode active material. The area between the first area 1021 and the second area 1022 is recorded as the middle area 1023. It is easy to understand that within the scope of the middle region 1023, there may be only the first negative electrode active material, only the second negative electrode active material, both the first negative electrode active material and the second negative electrode active material, or other negative electrode active materials known in the art in addition to the first negative electrode active material and the second negative electrode active material of the present application.

[0062] It should be understood that Figure 1 In the embodiment shown in FIG. 1 , the second surface 102 b contacts the upper surface of the negative electrode current collector 101 , but the structure of the negative electrode sheet of the present application is not limited thereto. For example, there may be an additional layer between the negative electrode film layer 102 and the negative electrode current collector 101 . In this case, the second surface 102 b does not directly contact the negative electrode current collector 101 .

[0063] It should also be understood that Figure 1 Although the graphic shows clear boundaries between areas, there may not be such clear interfaces in the product.

[0064] In some embodiments, the lithium insertion platform voltage of the first negative electrode active material is 0.123V to 0.135V. The lithium insertion rate of the battery is positively correlated with the electrode potential, that is, the larger the electrode potential, the larger the lithium insertion rate of the battery. The lithium insertion platform voltage is within this range, so that lithium insertion is performed at a relatively high voltage, which is beneficial to improving the kinetic performance of the secondary battery and is not prone to lithium precipitation.

[0065] In some embodiments, the carbon coating layer includes soft carbon. The lithium storage process of soft carbon is mainly the adsorption of active lithium ions in its structural defects, edges and micropores, which has relatively fast reaction kinetics. Therefore, it is beneficial to improve the kinetic performance of the secondary battery.

[0066] In the present application, the matrix and the carbon coating layer of the first negative electrode active material can be distinguished by transmission electron microscopy (TEM) of the material. In the transmission electron microscopy (TEM) image of the first negative electrode active material, the matrix has regular lattice fringes, while the carbon coating layer has no obvious lattice fringes and is soft carbon.

[0067] In the present application, primary particles and secondary particles have the meanings known in the art. Among them, primary particles refer to non-agglomerated particles, and secondary particles refer to agglomerated particles formed by the aggregation of two or more primary particles. Primary particles and secondary particles can be distinguished by using scanning electron microscopy (SEM) images.

[0068] In some embodiments, in the first negative electrode active material, the amount of secondary particle graphite material accounts for greater than or equal to 60%, such as 60%, 65%, 70%, 75%, 80% or a value between the ranges formed by any two of them. Optionally, the amount of secondary particle graphite material accounts for 75%, and two graphite materials (i.e., primary particle graphite material and secondary particle graphite material) are arranged in the negative electrode film layer region (i.e., the first region) away from the negative electrode current collector for use in combination, wherein the granulation structure of the secondary particle graphite material is conducive to reducing the OI value of the material, thereby facilitating fast charging performance, while the single particle graphite material (i.e., primary particle graphite material) is conducive to increasing the active specific surface area, reducing the charge transfer resistance (Rct), and further improving the fast charging performance of the battery. By using secondary particles as the main material in the first negative electrode active material, the isotropy is high, so that the expansion of the secondary battery during the cycle can be dispersed in all directions, reducing the expansion of the pole piece and improving the cycle performance.

[0069] In some embodiments, the OI value of the first negative electrode active material powder is 2.0 to 6.0. Exemplarily, the OI value of the first negative electrode active material powder can be 2, 3, 4, 4.5, 5, 6, or a value between the ranges formed by any two of them. Optionally, the OI value of the first negative electrode active material powder is 4.5 to 6.0. As a result, lithium ions can be embedded from all directions, improving the charging capacity of the secondary battery.

[0070] In the present application, the powder optimization index (OI) is a quantitative index used to characterize the degree of crystal orientation of a powder sample. It evaluates the growth and arrangement of crystals by comparing the integral area of ​​the diffraction peak of the (004) crystal plane of crystalline carbon in the powder sample with the integral area of ​​the diffraction peak of the (110) crystal plane of crystalline carbon. The OI value can be measured using instruments and methods known in the art. For example, the X-ray diffraction pattern of the powder sample can be obtained by referring to JIS K 0131-1996 and JB / T 4220-2011, and the powder OI value of the sample can be calculated according to OI value = I(004) / I(110). I(004) is the integral area of ​​the diffraction peak of the (004) crystal plane of crystalline carbon in the powder sample, and I(110) is the integral area of ​​the diffraction peak of the (110) crystal plane of crystalline carbon in the powder sample. In the X-ray diffraction analysis test of the embodiment of the present application, a copper target can be used as an anode target, and CuKα rays can be used as a radiation source, with a ray wavelength of The scanning 2θ angle range was from 20° to 80°, and the scanning rate was 4° / min.

[0071] In some embodiments, the powder compaction density of the first negative electrode active material under a pressure of 50000 N is less than the powder compaction density of the second negative electrode active material under a pressure of 50000 N. Thus, the porosity of the first region is greater than the porosity of the second region, which is beneficial to increase the contact opportunity between the upper region and the active ions in the electrolyte, so that the active ions can migrate faster during the charge and discharge process, improve the lithium insertion kinetics of the material, and thus improve the fast charging performance of the battery.

[0072] In some embodiments, the powder compaction density of the first negative electrode active material under a pressure of 50000N is 1.74g / cc to 1.79g / cc. For example, the powder compaction density of the first negative electrode active material under a pressure of 50000N is 1.74g / cc, 1.75g / cc, 1.76g / cc, 1.79g / cc, or a value between the ranges of any two of these values. Thus, it is beneficial to provide an appropriate porosity in the first region, thereby facilitating the infiltration of the electrolyte, and further facilitating the improvement of the kinetic performance of the secondary battery.

[0073] In some embodiments, the powder compaction density of the second negative electrode active material under a pressure of 50000N is 1.95g / cc to 2.04g / cc. By making the powder compaction density of the second negative electrode active material within the above range, it is beneficial to provide appropriate porosity in the first region, and it is also beneficial to improve the energy density of the secondary battery. Exemplarily, the powder compaction density of the second negative electrode active material under a pressure of 50000N can be 1.95g / cc, 1.96g / cc, 1.97g / cc, 1.98g / cc, 1.99g / cc, 2.00g / cc, 2.01g / cc, 2.02g / cc, 2.03g / cc, 2.04g / cc or a value between any two of them.

[0074] In this application, the powder compaction density of a material is the mass per unit volume of the powder under specified conditions. It can be measured using instruments and methods known in the art. For example, it can be measured by an electronic pressure testing machine (for example, a UTM7305 electronic pressure testing machine) with reference to GB / T 24533-2009. An exemplary test method is as follows: weigh 1g of sample powder and add a bottom area of ​​1.327cm 2 In the mold, the pressure is increased to 50000N, the pressure is maintained for 30s, and then the pressure is released and maintained for 10s. Then the powder compaction density of the material under the pressure of 50000N is recorded and calculated.

[0075] In some embodiments, the volume distribution particle size Dv50 of the first negative electrode active material is 7.8 μm to 15.8 μm. By making the volume distribution particle size Dv50 of the first negative electrode active material in the above range, it is beneficial to form a better pore distribution state in the first region of the pole piece, which is more conducive to improving the transmission performance of ions and electrons and improving the fast charging performance of the battery. For example, the volume distribution particle size Dv50 of the first negative electrode active material is 7.8 μm, 8.0 μm, 8.5 μm, 9.0 μm, 9.5 μm, 10.0 μm, 10.5 μm, 11.0 μm, 11.5 μm, 12.0 μm, 12.5 μm, 15.8 μm or a value between the ranges consisting of any two of these values.

[0076] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the first negative electrode active material is 0.90 to 1.50. Thus, the particle size distribution is within this range, indicating that the negative electrode active material particles are well distributed, which is conducive to the upper region of the negative electrode film layer having a suitable pore structure, thereby reducing the difficulty of ion liquid phase transmission, thereby improving the kinetic performance of the secondary battery. For example, the particle size distribution (Dv90-Dv10) / Dv50 of the first negative electrode active material is 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50 or a value between the ranges consisting of any two of these values.

[0077] In this application, the volume distribution particle size Dv10, Dv50, and Dv90 of the material are well-known in the art, which respectively represent the particle size corresponding to the cumulative volume distribution percentage of the material reaching 10%, 50%, and 90%, and can be measured using instruments and methods known in the art. For example, it can be measured with a laser particle size analyzer with reference to GB / T 19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0078] In some embodiments, the BET specific surface area of ​​the first negative electrode active material is 0.6 m 2 / g to 1.3m 2 / g. By making the specific surface area of ​​the first negative electrode active material within the above range, on the one hand, the first negative electrode active material can have a lower surface side reaction activity, thereby reducing the consumption of active ions by SEI film formation and improving the initial coulombic efficiency of the secondary battery; on the other hand, it can also have a higher active ion transport performance and improve the kinetic performance of the secondary battery. For example, the BET specific surface area of ​​the first negative electrode active material is 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g or a value within a range consisting of any two of these values.

[0079] In this application, the specific surface area of ​​a material has a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be measured by nitrogen adsorption specific surface area analysis test method according to GB / T 19587-2017 and calculated using the BET (Brunauer Emmett Teller) method. The test instrument can be the Tri-Star 3020 specific surface area pore size analysis tester from Micromeritics, USA.

[0080] In some embodiments, the gram capacity of the first negative electrode active material is 350.5mAh / g to 358.5mAh / g, for example, the gram capacity of the first negative electrode active material is 350.5mAh / g, 351.0mAh / g, 352.0mAh / g, 353.0mAh / g, 354.0mAh / g, 355.0mAh / g, 356.0mAh / g, 357.0mAh / g, 358.0mAh / g, 358.5mAh / g or a value between the ranges of any two of these values. By making the gram capacity of the first negative electrode active material within the above range, it is beneficial for the secondary battery to have good power performance while taking into account energy density.

[0081] In this application, the gram capacity of the material is the ratio of the capacitance that the active material can release to the mass of the active material, which can be tested by methods known in the art. The exemplary test method is as follows: the sample powder is mixed with a conductive agent, a binder and other optional additives in a certain mass ratio with a solvent to form a slurry; the prepared slurry is applied on the surface of the negative electrode current collector copper foil, dried in an oven and set aside; the electrolytic salt is dissolved in an organic solvent to prepare an electrolyte of a certain concentration; then a metal lithium sheet is used as a counter electrode, a polyethylene (PE) film is used as a separator, and the electrolyte is assembled into a CR2430 button cell in an argon-protected glove box. After the obtained button battery was left to stand for 12 hours, it was discharged at a constant current of 0.15mA to 0.005V at 25°C, left to stand for 10 minutes, and then discharged at a constant current of 50μA to 0.005V, left to stand for 10 minutes, and then discharged at a constant current of 10μA to 0.005V; then charged to 2.0V at a constant current of 0.3mA, and the charging capacity was recorded. The ratio of the charging capacity to the mass of the sample is the gram capacity of the corresponding material. In some embodiments, the gram capacity of the second negative electrode active material is greater than 359mAh / g. Optionally, the gram capacity of the second negative electrode active material is 360mAh / g to 366mAh / g. By making the gram capacity of the second negative electrode active material within the above range, it is beneficial to increase the gram capacity of the negative electrode film layer, thereby increasing the energy density of the secondary battery. Exemplarily, the gram capacity of the second negative electrode active material can be 359 mAh / g, 360 mAh / g, 361 mAh / g, 362 mAh / g, 363 mAh / g, 364 mAh / g, 365 mAh / g, 366 mAh / g, or a value between the ranges formed by any two of them. In some embodiments, the La(110) of the second negative electrode active material is 130 nm to 175 nm, and the Lc(002) is 30 nm to 42 nm, wherein La(110) represents the crystallite size along the a-axis in the (110) crystal plane of the material, and Lc(002) represents the crystallite size along the c-axis in the (002) crystal plane of the material.

[0082] In the present application, the relatively large La of the second negative electrode active material indicates that the crystallite size of the second negative electrode active material is relatively large, so that the number of lithium-insertable sites on the surface increases, and therefore the gram capacity is higher. In addition, the larger crystallite size can also reduce the number of crystallite grain boundaries of the material, further increase the lithium-insertable sites, thereby reducing the adverse effects of the gram capacity and the powder compaction density, and thus improving the gram capacity and powder compaction density of the material. The Lc of the second negative electrode active material is within the above range, which is conducive to reducing the stacking of graphite crystallites, thereby reducing the number of grain boundaries between crystallites, increasing the lithium-insertion sites on the surface of the material, and thus improving the gram capacity of the material. As a result, the second negative electrode active material located in the second region has a high gram capacity and a high compaction density, which is conducive to the secondary battery having a high energy density. .

[0083] The La(110) of the second negative electrode active material is 130nm-175nm, and Lc(002) is 30nm-42nm. Exemplarily, La(110) is 130nm, 135nm, 140nm, 145nm, 150nm, 155nm, 160nm, 165nm, 170nm, 172nm, 173nm, 175nm, or a value between the ranges consisting of any two of them, and Lc(002) is 30nm, 31nm, 32nm, 33nm, 34nm, 35nm, 36nm, 37nm, 38nm, 39nm, 40nm, 41nm, 42nm, or a value between the ranges consisting of any two of them. Optionally, the La(110) of the second negative electrode active material is 132nm-172nm, and Lc(002) is 30nm-36nm. By making La(110) and Lc(002) of the second negative electrode active material within the above ranges, it is more advantageous to improve the gram capacity and compaction density of the second negative electrode active material, thereby facilitating the secondary battery to have a high energy density.

[0084] In the present application, the La (110) and Lc (002) of the material can be measured using instruments and methods known in the art. For example, the negative electrode plate removed from the secondary battery can be cleaned with an organic solvent such as DMC and then dried. The cleaned negative electrode plate is then immersed in NMP for ultrasonic treatment to separate the copper foil to obtain the negative electrode material. After the negative electrode material is dried, it is sintered at 350°C to 500°C, then washed with water for multiple times, and dried at 80°C to obtain the first negative electrode active material. An X-ray diffractometer (such as Bruker D8 Discover) is used for testing. The test can refer to JIS K 0131-1996 and JB / T4220-2011 to obtain the peak intensity and half-maximum full width (FWHM) of the diffraction peak corresponding to the (110) crystal plane of the first negative electrode active material, and the peak intensity and half-maximum full width (FWHM) of the diffraction peak corresponding to the (002) crystal plane, and then calculated according to the Scherrer formula.

[0085] In some embodiments, the La(110) / Lc(002) of the second negative electrode active material is 3.5 to 5.5. In the present application, by making the La(110) / Lc(002) of the second negative electrode active material within the above range, the number of crystallites in the material is small, and therefore the number of grain boundaries between the grains is small, which is beneficial to increase the lithium embedding sites on the surface of the material, improve the gram capacity of the material, and thus improve the energy density of the secondary battery. Exemplarily, La(110) / Lc(002) can be 3.5, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8, 5.0, 5.2, 5.5 or a value within the range consisting of any two of them. In some optional embodiments, in the second negative electrode active material, La(110) / Lc(002) is 4.5 to 5.5.

[0086] In some embodiments, charge and discharge tests are performed on a button cell prepared from the second negative electrode active material at a lithium desorption rate of 0.1C and a lithium insertion rate of 0.05C, respectively, to obtain a charge and discharge curve in the range of 0.005V to 2.0V. In the discharge curve, there is a lithium insertion platform in the voltage range of 0.005V to 0.07V, and the discharge capacity corresponding to the lithium insertion platform accounts for more than 43% of the total discharge capacity of the button cell.

[0087] In the present application, the charge and discharge test is carried out by the following method: the sample powder is mixed evenly with the conductive agent carbon black (SuperP), the binder polyvinylidene fluoride (PVDF) and the solvent N-methylpyrrolidone (NMP) in a mass ratio of 91.6:1.8:6.6 to prepare a slurry; the prepared slurry is coated on the surface of the negative electrode current collector copper foil, and dried in an oven for use; ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare a concentration of 1 mol / s. L electrolyte; then use the metal lithium sheet as the counter electrode and the polyethylene (PE) film as the isolation membrane, and assemble them into a CR2430 button cell with the above electrolyte in an argon-protected glove box; after the obtained button cell is allowed to stand for 12 hours, it is discharged at a constant current rate of 0.05C at 25°C to 0.005V, and then it is discharged at a constant current rate of 50μA again to 0.005V, and then it is discharged at a constant current rate of 10μA to 0.005V, and then it is discharged at a constant current rate of 10μA to 0.005V, and then it is discharged at a constant current rate of 0.1C to 2.0V, and the relationship between the charge and discharge capacity and voltage of the material, that is, the charge and discharge curve, is obtained.

[0088] In this application, the button cell prepared with the second negative electrode active material is subjected to the above-mentioned charge and discharge test to obtain the charge and discharge curve. In the discharge curve, the discharge capacity corresponding to the lithium insertion platform in the voltage range of 0.005V to 0.07V accounts for more than 43% of the total discharge capacity of the button cell. The high gram capacity of the second negative electrode active material is conducive to improving the energy density of the secondary battery. Although the mechanism is not clear, the inventor believes that during the lithium insertion process of the graphite material, as the amount of lithium ion insertion increases, graphite intercalation compounds of different orders, such as LiC 24 ,LiC 12 , LiC6, etc. The formation of graphite intercalation compounds of different orders corresponds to lithium insertion platforms in different voltage ranges in the charge and discharge curve of graphite materials. Due to the different theoretical capacities of graphite intercalation compounds of different orders, for example, the theoretical capacity of LiC6 is 372mAh / g, while LiC 12 The theoretical specific capacity is 186 mAh / g. Therefore, in the process of lithium insertion, the more LiC6 (i.e., the lithium insertion platform corresponding to the voltage range of 0.005V to 0.07V) is formed, the more the corresponding capacity contribution is, and the higher the gram capacity of the graphite material is. Exemplarily, X1 can be 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50% or a value between the ranges consisting of any two of them.

[0089] In some embodiments, the ratio X1 of the discharge capacity corresponding to the lithium embedded platform to the total discharge capacity of the button cell is 43% to 50%, optionally 43% to 47%.

[0090] In some embodiments, the degree of graphitization of the second negative electrode active material is 94.0% to 96.0%. By making the degree of graphitization of the second negative electrode active material in the above range, it is beneficial for the first negative electrode active material to have a high compaction density and gram capacity, thereby improving the energy density of the secondary battery. Exemplarily, the degree of graphitization of the second negative electrode active material can be 94.0%, 94.5%, 95.0%, 95.5%, 96.0% or a value between the ranges consisting of any two of them. In some optional embodiments, the degree of graphitization of the second negative electrode active material is 94.2% to 95.8%.

[0091] In the present application, the graphitization degree of a material is the proportion of carbon in the material in the form of a graphite structure, which can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used for testing. The test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d of the C(002) crystal plane in the material crystal structure. 002 Then according to the formula g = (0.344-d002 ) / (0.344-0.3354)×100% to calculate the graphitization degree. In the above formula, d 002 It is the average interlayer spacing of the C(002) crystal plane in the material's crystal structure expressed in nanometers (nm).

[0092] In some embodiments, the volume distribution particle size Dv50 of the second negative electrode active material is 14.5 μm to 18.0 μm, which can be measured by the above method. Exemplarily, the volume distribution particle size Dv50 of the first negative electrode active material can be 14.5 μm, 15.0 μm, 15.5 μm, 16.0 μm, 16.5 μm, 17.0 μm, 17.5 μm, 18.0 μm or a value between the ranges consisting of any two of them. In some optional embodiments, the volume distribution particle size Dv50 of the second negative electrode active material is 15.0 μm to 17.5 μm.

[0093] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the second negative electrode active material is 0.90-1.25. Exemplarily, the particle size distribution (Dv90-Dv10) / Dv50 of the second negative electrode active material is 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25 or a value between the ranges consisting of any two of them. In some optional embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the second negative electrode active material is 0.90-1.20.

[0094] In some embodiments, the specific surface area of ​​the second negative electrode active material is 0.8 m 2 / g~2.1m 2 / g, which can be measured by the above method. By making the specific surface area of ​​the second negative electrode active material within the above range, on the one hand, the second negative electrode active material can have a lower surface side reaction activity, thereby reducing the consumption of active ions by SEI film formation and improving the first coulomb efficiency of the secondary battery; on the other hand, it can also have a higher active ion transport performance and improve the kinetic performance of the secondary battery. Exemplarily, the specific surface area of ​​the second negative electrode active material can be 0.8m 2 / g, 1.0m 2 / g, 1.2m 2 / g, 1.4m 2 / g, 1.6m 2 / g, 1.8m 2 / g, 2.0m 2 / g, 2.1m 2 / g or a value between the ranges consisting of any two of them.

[0095] In some embodiments, in the negative electrode film layer, the mass ratio of the first negative electrode active material to the second negative electrode active material is 4:6 to 6:4. By making the mass ratio of the first negative electrode active material to the second negative electrode active material within the above range, it is beneficial for the secondary battery to have excellent kinetic performance while taking into account energy density. Exemplarily, the mass ratio of the first negative electrode active material to the second negative electrode active material can be 4:6, 5:5, 6:4 or a ratio between the ranges consisting of any two of these values.

[0096] In some embodiments, the compaction density of the negative electrode film layer is 1.50g / cc to 1.90g / cc. By making the compaction density of the powder of the negative electrode film layer within the above range, it is beneficial for the negative electrode film layer to take into account high capacity, good active ion and electron transport performance, and thus it is beneficial for the secondary battery to take into account high energy density and good kinetic performance. Exemplarily, the compaction density of the negative electrode film layer is 1.50g / cc, 1.55g / cc, 1.60g / cc, 1.65g / cc, 1.70g / cc, 1.75g / cc, 1.80g / cc, 1.85g / cc, 1.90g / cc or a value between the ranges consisting of any two of them. In some optional embodiments, the compaction density of the negative electrode film layer is 1.55g / cc to 1.85g / cc.

[0097] In some embodiments, the surface density of the negative electrode film layer is 6.0 mg / cm 2 ~24.0mg / cm 2 By making the surface density of the negative electrode film layer within the above range, it is beneficial for the negative electrode film layer to have both high capacity and good active ion and electron transport performance, and thus it is beneficial for the secondary battery to have both high energy density and good kinetic performance. For example, the surface density of the negative electrode film layer can be 6.0 mg / cm 2 、6.5mg / cm 2 、8.0mg / cm 2 、10.0mg / cm 2 、12.0mg / cm 2 、14.0mg / cm 2 、16.0mg / cm 2 、18.0mg / cm 2 、20.0mg / cm 2 、22.0mg / cm 2 、24.0mg / cm 2 Or a value between any two of the ranges formed by these values. In some optional embodiments, the surface density of the negative electrode film layer is 6.5 mg / cm 2 ~22.5mg / cm 2 .

[0098] In some embodiments, the thickness of the negative electrode film layer is 60 μm to 240 μm. By making the thickness of the negative electrode film layer within the above range, it is beneficial for the negative electrode film layer to take into account high capacity, high active ion and electron transport performance, which is beneficial for the secondary battery to take into account high energy density and good storage performance and kinetic performance. Exemplarily, the thickness of the negative electrode film layer can be 60 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 140 μm, 160 μm, 180 μm, 200 μm, 220 μm, 240 μm or a value between the ranges consisting of any two of them. In some optional embodiments, the thickness of the negative electrode film layer is 90 μm to 220 μm.

[0099] In this application, the thickness of the negative electrode film layer has a well-known meaning in the art and can be tested by methods known in the art, such as using a micrometer (such as Mitutoyo 293-100, with an accuracy of 0.1 μm). The thickness range given in this application is the thickness range of the negative electrode film layer on one side of the negative electrode current collector.

[0100] The membrane layer is configured as a double layer, and the porosity of the upper region (first region) is greater than the porosity of the lower region (second region), which is beneficial to increase the contact opportunity between the upper region and the active ions in the electrolyte, so that the active ions can migrate faster during the charge and discharge process, thereby improving the lithium insertion kinetics of the material and thus improving the fast charging performance of the battery.

[0101] In the present application, the porosity represents the number of pores per unit area in the channel from the membrane layer to the substrate, wherein the porosity of the first region and the second region can be tested by any method known in the art. Exemplarily, the cold pressed pole piece is sampled and subjected to cross-section polishing by a cross-section ion polisher (e.g., IB-09010CP argon ion cross-section polisher of JEOL, Japan), and then the longitudinal section of the negative pole piece is scanned by a scanning electron microscope (e.g., Sigma 300 scanning electron microscope of ZEISS, Germany); a plurality of test areas are randomly selected in the test sample, and images of the plurality of test areas are obtained by scanning electron microscope, and finally, the scanned images characterizing the first region and the second region are threshold segmented by using ImageJ software, and the gray-white contrast area is the particle, and the black contrast area is the pore. By computer image recognition, the pore part is analyzed by the threshold division method to obtain the porosity of different depth areas on the surface of the pole piece. Alternatively, the battery can be disassembled to obtain the negative electrode sheet, which is cut into 6 mm*6 mm size and fixed on a sample holder, and the cross section of the negative electrode sheet is prepared by a cross section ion polisher (e.g., IB-09010CP argon ion cross section polisher of JEOL, Japan). Then, a scanning electron microscope (e.g., Sigma 300 scanning electron microscope of ZEISS, Germany) is used for scanning, and the pore part is analyzed by computer image recognition and threshold division method to obtain the porosity of different depth areas on the surface of the electrode sheet.

[0102] In some embodiments, in the first negative electrode active material, the mass percentage of the carbon coating layer relative to the mass of the substrate is 0.52% to 2.35%.

[0103] In some embodiments, the method for preparing the first negative electrode active material comprises:

[0104] Providing a base material;

[0105] After mixing the base material and the organic carbon source, heat treatment is performed to obtain the first negative electrode active material;

[0106] Wherein, the mass ratio of the matrix material to the organic carbon source is 100:1.5 to 100:8.

[0107] Thus, by setting the matrix material and the organic carbon source within the above mass ratio range, the lithium insertion platform voltage of the obtained first negative electrode active material is made to be 0.118V to 0.140V.

[0108] Positive electrode

[0109] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes a positive electrode active material.

[0110] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0111] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0112] In some embodiments, when the battery cell is a lithium secondary battery, the positive electrode active material may adopt a positive electrode active material for lithium secondary batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi0.85 Co 0.1 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0113] In some embodiments, when the battery cell is a sodium secondary battery, the positive electrode active material may be a positive electrode active material for a sodium secondary battery known in the art. As an example, the positive electrode active material may include sodium transition metal oxides, polyanionic compounds, Prussian blue compounds, and the like.

[0114] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.

[0115] In the list of positive electrode active materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.

[0116] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0117] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0118] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0119] Electrolytes

[0120] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0121] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0122] In some embodiments, the electrolyte salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0123] In some embodiments, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0124] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0125] Isolation film

[0126] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0127] In some embodiments, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0128] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0129] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0130] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0131] The present application has no particular restrictions on the shape of the battery cell, which can be cylindrical, square or any other shape. For example, Figure 2 The battery cell 5 is a square structure as an example.

[0132] In some embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0133] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0134] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0135] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0136] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0137] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0138] Method for preparing secondary battery

[0139] The present application also provides a method for preparing a secondary battery, which includes preparing a negative electrode plate.

[0140] The negative electrode sheet can be prepared in the following manner: provide a first slurry containing a first negative electrode active material and a second slurry containing a second negative electrode active material; extrude the first slurry and the second slurry simultaneously, coat the first slurry on the negative electrode collector copper foil, and coat the second slurry on the first slurry; after drying and cold pressing, obtain the negative electrode sheet.

[0141] Wherein, preparing the first negative electrode active material comprises:

[0142] Providing a base material;

[0143] After mixing the base material and the organic carbon source, heat treatment is performed to obtain the first negative electrode active material;

[0144] The mass ratio of the matrix material to the organic carbon source is 100:1.5 to 100:8, for example, 100:1.5, 100:2, 100:3, 100:4, 100:5, 100:6, 100:8 or a value within a range consisting of any two of these values.

[0145] Thus, by setting the matrix material and the organic carbon source within the above mass ratio range, the mass percentage of the carbon coating layer in the obtained first negative electrode active material relative to the mass of the matrix is ​​0.52% to 2.35%, thereby making its lithium insertion platform voltage within the range of 0.118V to 0.140V.

[0146] In the present application, the "surface carbon residue amount" after heat treatment is taken as the "amount of carbon coating layer", and the calculation process of the mass percentage of the carbon coating layer is illustrated by taking asphalt as the raw material of the carbon coating layer in the preparation process as an example.

[0147] The amount of residual carbon on the surface = the amount of asphalt added × the coking value of asphalt.

[0148] The mass percentage of the carbon coating layer = the amount of residual carbon on the surface / the mass of the substrate × 100%.

[0149] For example, the preparation method of the first negative electrode active material may be, for example, the following method, which includes steps (11) to (12):

[0150] Step (11) provides a base material.

[0151] In some embodiments, step (11) includes steps (111) to (113).

[0152] Step (111): crushing, shaping and classifying the artificial graphite precursor to obtain primary particles.

[0153] In some embodiments, the artificial graphite precursor in step (111) includes at least one of calcined coke and needle coke.

[0154] In some embodiments, the volume average particle size Dv50 of the primary particles in step (111) is 6.0 μm to 9.0 μm, for example, 6.0 μm, 6.5 μm, 7.0 μm, 7.5 μm, 8.0 μm, 8.5 μm, 9.0 μm or a value in a range consisting of any two of these values.

[0155] Step (112): mixing the first binder and the primary particles, granulating, and then subjecting the granulated product to a first heat treatment to obtain a secondary particle graphite material.

[0156] The present application does not specifically limit the type of the first binder, and any binder known in the art may be used. For example, the second binder may include solid asphalt, liquid asphalt, and the like.

[0157] In some embodiments, the mixing mass ratio of the primary particles to the first binder is 100:5 to 100:9, for example, 100:5, 100:6, 100:7, 100:8, 100:9, or a value in a range consisting of any two of these values.

[0158] In some embodiments, the first heat treatment includes graphitizing at 2800°C to 3800°C.

[0159] Those skilled in the art can adjust the graphitization time as needed. For example, an Acheson graphitization furnace can be used for graphitization treatment, and when the temperature is above 2800° C., the graphitization time can be 2 to 8 days.

[0160] Step (113): Mix the primary particles and the secondary particles to obtain a matrix material.

[0161] The purpose of mixing primary particles with secondary particles is to fill the primary particles between the secondary particles. Since the primary particles have a small particle size and the secondary particles have a large particle size, the stacking and filling advantages of the two are complementary, thereby improving the migration rate of active ions on the surface / bulk of the obtained first negative electrode active material.

[0162] In some embodiments, the amount of secondary particles in the matrix material accounts for more than 60%.

[0163] Step (12) After mixing the base material and the organic carbon source, a second heat treatment is performed to obtain a first negative electrode active material.

[0164] In some embodiments, the mass ratio of the matrix material to the organic carbon source is 100:1.5 to 100:8.

[0165] The present application does not specifically limit the type of organic carbon source, and carbon-containing substances known in the art can be used. For example, the organic carbon source includes at least one of coal tar, petroleum tar, and phenolic resin.

[0166] In some embodiments, the second heat treatment includes a carbonization treatment at 900° C. to 1300° C. for 1 h to 5 h.

[0167] The preparation method of the second negative electrode active material in the present application may, for example, be the following method, comprising the following steps (21) to (23):

[0168] Step (21): crushing and classifying the artificial graphite precursor to obtain a first intermediate.

[0169] Step (22): The first intermediate is mixed with the second binder and granulated, and then subjected to a third heat treatment to obtain a second intermediate.

[0170] Step (23): subjecting the second intermediate to a fourth heat treatment to obtain a second negative electrode active material.

[0171] In the present application, an artificial graphite precursor refers to a raw material for preparing a second negative electrode active material. The present application does not specifically limit the type of artificial graphite precursor, and an artificial graphite precursor known in the art may be used. For example, the artificial graphite precursor includes one or more of calcined coke, petroleum non-needle coke, petroleum needle coke, coal non-needle coke, and coal needle coke. Among them, calcined coke includes coke formed by calcining the above-mentioned petroleum non-needle coke, petroleum needle coke, coal non-needle coke, and coal needle coke. In some optional embodiments, calcined needle coke may be used.

[0172] The present application does not specifically limit the methods of crushing, shaping and grading, and the methods of crushing, shaping and grading known in the art can be used.

[0173] In some embodiments, calcined coke can be used as an artificial graphite precursor in step (21). Calcined coke has strong needle-like properties and less mosaic structure. Using it as an artificial graphite precursor helps the development of the grain structure during the graphitization process, thereby obtaining a second negative electrode active material with a larger La and / or a higher degree of graphitization, thereby promoting the embedding of lithium ions between the layers of the second negative electrode active material, and is also beneficial to the formation of a large amount of LiC6 during the lithium embedding process of the second negative electrode active material.

[0174] In some embodiments, the volume average particle size Dv50 of the first intermediate obtained in step (21) is 9.0 μm to 13.0 μm, for example, 9.0 μm, 10.0 μm, 11.0 μm, 12.0 μm, 13.0 μm, or a value between any two of these values.

[0175] In some embodiments, the mixing mass ratio of the second intermediate to the first binder is 100:8 to 100:12, for example, 100:8, 100:9, 100:10, 100:11, 100:12 or a value between ranges consisting of any two of these values.

[0176] In some embodiments, the volume average particle size Dv50 of the second intermediate is 15 μm to 18 μm, for example, 15 μm, 16 μm, 17 μm, 18 μm, or a value in a range consisting of any two of these values.

[0177] In some embodiments, the second adhesive includes asphalt with strong adhesion, low residual carbon and easy graphitization. By selecting the above asphalt as the second adhesive, the residual amount of asphalt in the second negative electrode active material can be reduced. Based on the easy graphitization characteristics of asphalt, the residual carbon of the asphalt after graphitization has a higher degree of graphitization, reducing the influence of the residual carbon on the gram capacity and compaction density of the second negative electrode active material.

[0178] In some embodiments, the third thermal treatment includes performing a pre-carbonization treatment at 1000° C. to 1500° C. for 1 hour to 4 hours.

[0179] In some embodiments, the fourth heat treatment includes graphitization at 3000° C. to 3200° C.

[0180] Those skilled in the art can adjust the graphitization time as needed. For example, an Acheson graphitization furnace can be used for graphitization treatment, and when the temperature is above 2800° C., the graphitization time can be 2 to 8 days.

[0181] In some embodiments, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0182] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0183] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0184] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0185] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0186] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material (artificial graphite), the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0187] Electrical devices

[0188] In addition, the present application also provides an electric device, which includes a secondary battery provided in the present application. The secondary battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0189] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0190] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0191] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.

[0192] Example

[0193] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0194] Preparation of the first negative electrode active material

[0195] Preparation Example 1-1

[0196] Step (11): Providing a matrix material comprises: Step (111) crushing and shaping needle-shaped green coke by air flow milling to obtain primary particles with a volume average particle size Dv50 of 8.5 μm. Step (112) mixing the primary particles with asphalt in a mass ratio of 100:8 and granulating the mixture, and then heat treating the granulated product at 3000° C. for 7 days to obtain secondary particles. Step (113) blending the secondary particles with the primary particles in a quantity ratio of 3:1 to obtain a matrix material.

[0197] Step (22) The blended matrix material is mixed with asphalt (coking value 33%) in a mass ratio of 100:2, and then carbonized at 1150° C. in a nitrogen atmosphere for 4 hours. Finally, the first negative electrode active material having a soft carbon coating structure on the surface is obtained through screening.

[0198] Preparation Examples 1-2 to 1-6

[0199] The preparation methods of Preparation Examples 1-2 to 1-6 are similar to Preparation Example 1-1, except that the mass ratio of the blended materials to the organic carbon source is adjusted according to the values ​​in Table 1 below.

[0200] Table 1

[0201] project raw material Mass ratio of matrix to organic carbon source serial number Preparation Example 1-1 Needle coke 100:2 Materials 1-1 Preparation Example 1-2 Needle coke 100:6 Materials 1-2 Preparation Example 1-3 Needle coke 100:1.5 Ingredients 1-3 Preparation Example 1-4 Needle coke 100:7 Ingredients 1-4 Preparation Example 1-5 Needle coke 100:8 Ingredients 1-5 Preparation Example 1-6 Needle coke 100:0 Materials 1-6

[0202] Test of the parameters of the first negative electrode active material

[0203] (1) Test of lithium embedded platform voltage X2:

[0204] The prepared first negative electrode active material (material 1-1), conductive agent carbon black (Super P), binder polyvinylidene fluoride (PVDF) are mixed uniformly with solvent N-methylpyrrolidone (NMP) in a mass ratio of 91.6:1.8:6.6 to prepare a slurry; the prepared slurry is coated on the surface of the negative electrode current collector copper foil, dried in an oven and set aside; ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L; then a metal lithium sheet is used as a counter electrode and a polyethylene (PE) film is used as an isolation membrane, and the above electrolyte is assembled into a CR2430 button battery in an argon-protected glove box; the obtained button battery is left to stand for 12 hours.

[0205] At 25°C, discharge at a constant current of 0.05C to 0.005V, let stand for 5 minutes, then discharge at a constant current of 50μA to 0.005V, let stand for 5 minutes, then discharge at a constant current of 10μA to 0.005V; then charge at a constant current of 0.1C to 2.0V, and obtain the relationship between the charge and discharge capacity and voltage of the material, that is, the charge and discharge curve. The total lithium insertion energy within 0.005V-2V in the discharge curve is recorded as E1, the total lithium insertion capacity within 0.005V-2.0V is recorded as C3, and the lithium insertion platform voltage X2 = E1 / C3.

[0206] The charge-discharge curve of material 1-1 measured by the above method is as follows Figure 8 As shown in the black curve in FIG, the total lithium insertion energy E1 within 0.005V-2V and the total lithium insertion capacity C3 within 0.005V-2.0V are calculated using the Blue Battery Test System (CT2001A), and the lithium insertion platform voltage is calculated to be 0.123V. The test results are recorded in Table 2.

[0207] The charge-discharge curves of materials 1-6 measured by the above method are as follows: Figure 8 As shown in the red curve in FIG, the total lithium insertion energy E1 within 0.005V-2V and the total lithium insertion capacity C3 within 0.005V-2.0V are calculated using the Blue Battery Test System (CT2001A), and the lithium insertion platform voltage is calculated to be 0.095V. The test results are recorded in Table 2.

[0208] from Figure 8 It can be seen that compared with material 1-6, material 1-1 has a carbon coating layer on the surface, and material 1-1 has an improved lithium insertion platform voltage.

[0209] (2) Powder OI value test:

[0210] The X-ray diffraction pattern of the powder sample can be obtained by referring to JIS K 0131-1996 and JB / T 4220-2011, and the powder OI value of the sample can be calculated according to OI value = I(004) / I(110). I(004) is the integral area of ​​the diffraction peak of the (004) crystal plane of the crystalline carbon in the powder sample, and I(110) is the integral area of ​​the diffraction peak of the (110) crystal plane of the crystalline carbon in the powder sample. In the X-ray diffraction analysis test, a copper target is used as the anode target, and CuKα rays are used as the radiation source. The wavelength of the ray is The scanning 2θ angle range was 20° to 80°, and the scanning rate was 4° / min. The test results are recorded in Table 2.

[0211] (3) BET specific surface area test:

[0212] It can refer to GB / T 19587-2017, use the nitrogen adsorption specific surface area analysis test method to test, and calculate it using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis test can be performed using the Tri-Star 3020 specific surface area pore size analysis tester from Micromeritics, USA.

[0213] (4) Compaction density test:

[0214] Weigh 1g of sample powder and add a bottom area of ​​1.327cm 2 The mold was pressurized to 50000N, maintained for 30s, then released and maintained for 10s. The powder compaction density of the material under a pressure of 50000N was then recorded and calculated. The test results are recorded in Table 4.

[0215] (5) Morphology test

[0216] After the material 1-1 prepared in Example 1 was subjected to focused ion beam (FIB) thinning pretreatment, Pt nanoparticles were used as the substrate and high-resolution testing was performed using a Thermo Scientific-Talos F200S G2 model field emission transmission electron microscope (TEM). The test results can be seen in Fig.10 .

[0217] from Fig.10 It can be seen that material 1-1 has a graphite core and an amorphous carbon layer (without obvious lattice fringes) located on its surface, that is, a soft carbon layer.

[0218] Table 2

[0219]

[0220]

[0221] Preparation Example 2-1

[0222] Preparation of the Second Negative Electrode Active Material

[0223] In step (21), the oil-based calcined needle coke raw material (carbon content of 98.5%, volatile content of 1.0%, sulfur content of 0.5%) is crushed and shaped by air jet mill to obtain a shaped material with a Dv50 of 11 μm (the first intermediate).

[0224] In step (22), granulating asphalt (softening point of 200°C; coking value of 60%) is used as a granulating agent to granulate the above-mentioned shaping material together through a granulating kettle to obtain a granulated material, wherein the mass ratio of the shaping material to the granulating agent is 100:8. After pre-carbonization at 1150°C in a nitrogen atmosphere for 2 hours, a second intermediate (volume distribution particle size Dv50 is 16.5 μm) is obtained.

[0225] Step (23) The second intermediate is graphitized at a high temperature of 3020° C., and the graphitized particles are sieved and demagnetized to obtain a second negative electrode active material (material 2-1).

[0226] Preparation Examples 2-2 and 2-3

[0227] The preparation methods of Preparation Examples 2-2 and 2-3 are similar to Preparation Example 2-1, except that the raw materials and graphitization temperature used in the preparation step of the second negative electrode active material are adjusted according to the values ​​in Table 3 below.

[0228] Table 3

[0229]

[0230] Test of parameters of the second negative electrode active material

[0231] (1) Testing of La and Lc:

[0232] Referring to the test method of JIS K 0131-1996, the test was carried out using a Bruker D8 Discover X-ray diffractometer, in which a copper target was used as the anode target, CuKα rays were used as the radiation source, and the ray wavelength was The scanning 2θ angle range is 20°-80°, and the scanning rate is 4° / min to obtain the X-ray diffraction pattern of the powder sample. La(110) calculation formula:

[0233]

[0234] Wherein: K is the shape factor, which is 1.84; λ is the wavelength (nm); β110 is the half-peak width of the 110 crystal plane corresponding to ~43° in the X-ray diffraction pattern; θ110 is the diffraction angle corresponding to the 110 crystal plane in the X-ray diffraction pattern.

[0235] Lc(002) calculation formula:

[0236] Where: K is the shape factor, which is 0.89; λ is the wavelength (nm); β002 is the half-peak width of the 002 crystal plane corresponding to 26° in the X-ray diffraction pattern; θ002 is the diffraction angle corresponding to the 002 crystal plane in the X-ray diffraction pattern. The test results are shown in Table 4.

[0237] (2) Test of gram capacity of materials:

[0238] The prepared second negative electrode active material, conductive agent carbon black (Super P), binder polyvinylidene fluoride (PVDF) and solvent N-methylpyrrolidone (NMP) are mixed uniformly in a mass ratio of 91.6:1.8:6.6 to prepare a slurry; the prepared slurry is coated on the surface of the negative electrode current collector copper foil, dried in an oven and set aside; ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L; then a metal lithium sheet is used as a counter electrode and a polyethylene (PE) film is used as an isolation membrane, and the above electrolyte is assembled into a CR2430 button battery in an argon-protected glove box; the obtained button battery is left to stand for 12 hours.

[0239] At 25°C, the button cell prepared above was first discharged to 0.005V at a current of 0.15mA, left to stand for 5 minutes, then discharged to 0.005V at a current of 50μA, left to stand for 5 minutes, and then discharged to 0.005V at a constant current of 10μA, and the first cycle discharge capacity of the button cell was recorded; then, the button cell was charged to 2.0V at a current of 0.3mA, and the first cycle charge capacity of the button cell was recorded. The ratio of the first cycle charge capacity to the mass of the material is the gram capacity of the material. The test results are recorded in Table 4.

[0240] (3) Test of the proportion of the platform's lithium-ion capacity to the overall capacity X1:

[0241] The CR2430 button cell was prepared by the same method as in the above-mentioned gram capacity test method. After the above-mentioned CR2430 button cell was allowed to stand for 12 hours, it was first discharged at a constant current of 0.15 mA to 0.005 V at 25°C, allowed to stand for 5 minutes, and then discharged at a constant current of 50 μA to 0.005 V again, allowed to stand for 5 minutes, and then discharged at a constant current of 10 μA to 0.005 V again; then it was charged at a constant current of 0.3 mA to 2.0 V, and the relationship between the charge and discharge capacity and voltage of the material was obtained, that is, the charge and discharge curve. The lithium insertion capacity of the lithium insertion platform that appears within 0.005V-0.070V in the discharge curve is recorded as C1, and the total lithium insertion capacity within the range of 0.005V-2.0V is recorded as C2, then the lithium insertion capacity of the platform accounts for X1=C1 / C2*100%.

[0242] The charge-discharge curve of material 2-1 measured by the above method is as follows Fig. 9 .from Fig. 9 The lithium insertion capacity of the lithium insertion platform in the range of 0.005V-0.070V in the discharge curve can be read as C1, and the total lithium insertion capacity in the range of 0.005V-2.0V is recorded as C2, and then the lithium insertion capacity proportion of the platform is calculated to be X1=44.1%. The test results are recorded in Table 4.

[0243] (4) Powder compaction density:

[0244] Weigh 1g of sample powder and add a bottom area of ​​1.327cm 2 The mold was pressurized to 50000N, maintained for 30s, then released and maintained for 10s. The powder compaction density of the material under a pressure of 50000N was then recorded and calculated. The test results are recorded in Table 4.

[0245] Table 4

[0246]

[0247] Example 1

[0248] Preparation of secondary batteries

[0249] (1) Preparation of negative electrode sheet:

[0250] The negative electrode active material (material 1-1) used in the first region, conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber were fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 97.0:0.80:1.0:1.2 to form a first negative electrode slurry.

[0251] The negative electrode active material (material 2-1) used in the second region, conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber were fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 96.4:1.0:1.2:1.4 to form a second negative electrode slurry.

[0252] The first negative electrode slurry and the second negative electrode slurry of the same mass are extruded simultaneously through an extrusion coating device, the first negative electrode slurry is coated on the negative electrode current collector copper foil, and the second negative electrode slurry is coated on the first negative electrode slurry; after drying and cold pressing, the negative electrode sheet is obtained. The coating weight of the first negative electrode slurry and the second negative electrode slurry is the same, the compaction density of the negative electrode film layer is 1.75g / cc, and the surface density of the negative electrode film layer is 11.5mg / cm 2 , the thickness of the negative electrode film layer is 65μm.

[0253] (2) Preparation of positive electrode sheet:

[0254] Lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 96:2:2, and then solvent N-methylpyrrolidone was added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on both surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained.

[0255] (3) Isolation film:

[0256] A 12 μm polyethylene film was used as the separator.

[0257] (4) Preparation of electrolyte:

[0258] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0259] (5) Assembly of secondary batteries:

[0260] The positive electrode sheet and negative electrode sheet prepared as above are placed in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then the electrode assembly is obtained by winding; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and a secondary battery is obtained after vacuum packaging, standing, forming, shaping and other processes.

[0261] Negative electrode testing

[0262] After cold pressing, the negative electrode piece is sampled and polished by a cross-section ion polisher (e.g., IB-09010CP argon ion cross-section polisher from JEOL, Japan), and then a longitudinal cross-section of the negative electrode piece is scanned by a scanning electron microscope (e.g., Sigma 300 scanning electron microscope from ZEISS, Germany), to obtain the following: Fig.11 SEM images shown.

[0263] from Fig.11 It can be seen that the porosity of the first region of the negative electrode sheet prepared in Example 1 is greater than the porosity of the second region.

[0264] Secondary battery performance test

[0265] (1) Fast charging capability (fast charging) test:

[0266] ① At 25°C, charge the secondary battery at a constant current of 0.33C to 3.8V, then charge at a constant voltage to a current of 0.05C. After standing for 5 minutes, discharge the secondary battery at a constant current of 0.33C to 2.0V, and record its actual capacity as C0.

[0267] ②Then the secondary battery is charged with a constant current of 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, and 3.0C0 in sequence to a negative electrode cut-off potential of 3.8V or 0V (whichever is reached first). After each charging is completed, it is necessary to discharge at 1C0 to 2.0V, and record the negative electrode potential corresponding to charging to 10% SOC, 20% SOC, 30% SOC, 40% SOC, 50% SOC, 60% SOC, 70% SOC, and 80% SOC (State of Charge) at different charging rates.

[0268] ③ Draw the charging rate-negative electrode potential curve under different SOC states, and obtain the charging rate corresponding to the negative electrode potential of 0V under different SOC states after linear fitting. The charging rate is the charging window under the SOC state, which is recorded as C 10%SOC , C 20%SOC , C 30%SOC , C 40%SOC , C 50%SOC , C 60%SOC , C 70%SOC , C 80%SOC .

[0269] ④ According to the following formula, the charging time T of the secondary battery from 10% SOC to 80% SOC (assuming that the secondary battery does not deposit lithium) is calculated, in minutes.

[0270] (60 / C 20%SOC+60 / C 30%SOC +60 / C 40%SOC +60 / C 50%SOC +60 / C 60%SOC +60 / C 70%SOC +60 / C 80%SOC )×10%.

[0271] (2) Energy density test:

[0272] At 25°C, the secondary battery was charged to 3.65V at 1 / 3C constant current, then charged to 0.05C at 3.65V, left to stand for 5 minutes, and then discharged to 2.5V at 1 / 3C constant current, and the battery discharge energy was recorded. The battery discharge energy divided by the battery weight is the battery weight energy density, in Wh / kg. The measurement data is shown in Table 5.

[0273] (3) Cycle performance test:

[0274] ① At 45°C, the secondary battery prepared above was left to stand for 5 minutes, and then charged at a constant current rate of 1C to the upper cut-off voltage (corresponding to 100% SOC);

[0275] ② Charge the secondary battery at a constant voltage to a current of 0.05C. After standing for 5 minutes, discharge the secondary battery at a constant current of 1C to the lower cut-off voltage (corresponding to 0% SOC). Record the discharge capacity at this time, which is the first cycle discharge capacity (D1).

[0276] Repeat the above steps ① and ② 1000 times, and record the discharge capacity D at the 1000th cycle. 1000 ;

[0277] Capacity retention rate of secondary battery after 1000 cycles (%) = D1 / D 1000 The test data are recorded in Table 5.

[0278] Embodiment 2-8

[0279] A secondary battery was prepared in the same manner as in Example 1, except that the types of active materials used in the second region and the first region were adjusted according to the description in Table 5.

[0280] The test results of the secondary batteries of Examples 2-8 are recorded in Table 5.

[0281] Comparative Examples 1-3

[0282] A secondary battery was prepared in the same manner as in Example 1, except that the types of active materials used in the second region and the first region were adjusted according to the description in Table 5.

[0283] Comparative Example 4

[0284] A secondary battery was prepared in the same manner as in Example 1, except that the negative electrode was prepared by the following method:

[0285] The negative electrode active material (material 1-1), conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber were fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 97.0:0.80:1.0:1.2 to form a negative electrode slurry.

[0286] The negative electrode slurry is coated on the negative electrode current collector copper foil through an extrusion coating device; after drying and cold pressing, the negative electrode sheet is obtained. The compaction density of the negative electrode film layer is 1.75g / cc, and the surface density of the negative electrode film layer is 11.5mg / cm 2 , the thickness of the negative electrode film layer is 65μm.

[0287] Comparative Example 5

[0288] A secondary battery was prepared in the same manner as in Example 1, except that the negative electrode was prepared by the following method:

[0289] The negative electrode active material (material 1-1+material 2-2, mass ratio of 1:1), conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber were fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 97.0:0.80:1.0:1.2 to form a negative electrode slurry.

[0290] The negative electrode slurry is coated on the negative electrode current collector copper foil through an extrusion coating device; after drying and cold pressing, the negative electrode sheet is obtained. The compaction density of the negative electrode film layer is 1.75g / cc, and the surface density of the negative electrode film layer is 11.5mg / cm 2 , the thickness of the negative electrode film layer is 65μm.

[0291] The test results of the secondary batteries of Comparative Examples 1-5 are recorded in Table 5.

[0292] Table 5

[0293]

[0294]

[0295] It can be seen from the data in Table 5 that compared with comparative examples 1-5, embodiments 1-8 in accordance with the present application can effectively improve the kinetic performance while taking into account high energy density without affecting the cycle performance.

[0296] Examples 9-10

[0297] A secondary battery was prepared and tested in a similar manner to Example 1, with the only difference being that when preparing the negative electrode sheet, the mass ratio of the first negative electrode active material to the second negative electrode active material was adjusted as recorded in Table 6.

[0298] The secondary battery was tested and the test results are recorded in Table 6.

[0299] Table 6

[0300]

[0301] It can be seen from the data in Table 6 that when the mass ratio of the first negative electrode active material to the second negative electrode active material is 4:6-6:4, the prepared secondary battery has improved kinetic performance while taking into account energy density.

[0302] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A secondary battery, comprising a negative electrode plate, characterized in that: The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer has a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, the thickness of the negative electrode film layer is recorded as H, the area within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the first area of ​​the negative electrode film layer, and the area within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the second area of ​​the negative electrode film layer, the first area includes a first negative electrode active material, and the second area includes a second negative electrode active material, The first negative electrode active material comprises a substrate and a carbon coating layer formed on at least a portion of the surface of the substrate; and the lithium insertion platform voltage of the first negative electrode active material is 0.118V to 0.140V, wherein the lithium insertion platform voltage is obtained by performing charge and discharge tests on button cells prepared from the test material under conditions of a lithium removal rate of 0.1C and a lithium insertion rate of 0.05C, respectively, to obtain a charge and discharge curve within the range of 0.005V-2.0V, wherein the ratio of the total lithium insertion energy within 0.005V-2.0V to the total lithium insertion capacity is defined as the lithium insertion platform voltage of the tested material; The gram capacity of the second negative electrode active material is greater than the gram capacity of the first negative electrode active material.

2. The secondary battery according to claim 1, characterized in that: The lithium insertion platform voltage of the first negative electrode active material is 0.123V to 0.135V.

3. The secondary battery according to claim 1 or 2, characterized in that: The carbon coating layer includes soft carbon.

4. The secondary battery according to any one of claims 1 to 3, characterized in that: The first negative electrode active material includes a primary particle graphite material and a secondary particle graphite material.

5. The secondary battery according to claim 4, characterized in that: In the first negative electrode active material, the secondary graphite particle material accounts for more than or equal to 60%.

6. The secondary battery according to any one of claims 1 to 5, characterized in that: The OI value of the first negative electrode active material powder is 2.0-6.

0.

7. The secondary battery according to any one of claims 1 to 6, characterized in that: The gram capacity of the second negative electrode active material is greater than 359 mAh / g.

8. The secondary battery according to any one of claims 1 to 7, characterized in that: The gram capacity of the second negative electrode active material is 360 mAh / g to 366 mAh / g.

9. The secondary battery according to any one of claims 1 to 8, characterized in that: The first negative electrode active material has a powder compaction density of 1.74 g / cc to 1.79 g / cc at a pressure of 50000 N; and / or The powder compaction density of the second negative electrode active material under a pressure of 50000N is 1.95 g / cc to 2.04 g / cc.

10. The secondary battery according to any one of claims 1 to 9, characterized in that: The first negative electrode active material satisfies one or more of the following: (1) the volume distribution particle size Dv50 of the first negative electrode active material is 7.8 μm to 15.8 μm; (2) the particle size distribution of the first negative electrode active material (Dv90-Dv10) / Dv50 is 0.90 to 1.50; (3) The BET specific surface area of ​​the first negative electrode active material is 0.6 m 2 / g to 1.3m 2 / g; (4) The gram capacity of the first negative electrode active material is 350.5 mAh / g to 358.5 mAh / g.

11. The secondary battery according to any one of claims 1 to 10, characterized in that: The second negative electrode active material satisfies one or more of the following: (1) The La(110) of the second negative electrode active material is 130 nm to 175 nm, and the Lc(002) is 30 nm to 42 nm, wherein La(110) represents the crystallite size along the a-axis in the (110) crystal plane of the material, and Lc(002) represents the crystallite size along the c-axis in the (002) crystal plane of the material; (2) La(110) / Lc(002) is 3.5 to 5.5; (3) performing charge and discharge tests on a button cell prepared from the second negative electrode active material at a lithium removal rate of 0.1C and a lithium insertion rate of 0.05C, respectively, to obtain a charge and discharge curve in the range of 0.005V to 2.0V, wherein in the discharge curve of the second negative electrode active material, a lithium insertion platform exists in the voltage range of 0.005V to 0.070V, and the discharge capacity corresponding to the lithium insertion platform accounts for a proportion X1 of more than 43% of the total discharge capacity of the button cell; (4) The second negative electrode active material has a degree of graphitization of 94.0% to 96.0%.

12. The secondary battery according to claim 11, characterized in that: The second negative electrode active material satisfies one or more of the following: (1) The La(110) of the second negative electrode active material is 132nm-172nm, and the Lc(002) is 30nm-36nm; (2) La(110) / Lc(002) is 4.5-5.5; (3) The ratio X1 of the discharge capacity corresponding to the lithium embedded platform to the total discharge capacity of the button battery is 43% to 47%; (4) The second negative electrode active material has a degree of graphitization of 94.2% to 95.8%.

13. The secondary battery according to any one of claims 1 to 12, characterized in that: The second negative electrode active material satisfies one or more of the following: (1) the volume distribution particle size Dv50 of the second negative electrode active material is 14.5 μm to 18.0 μm; (2) the particle size distribution of the second negative electrode active material (Dv90-Dv10) / Dv50 is 0.9 to 1.25; (3) The BET specific surface area of ​​the second negative electrode active material is 0.8 m 2 / g~2.1m 2 / g.

14. The secondary battery according to any one of claims 1 to 13, characterized in that: In the negative electrode film layer, the mass ratio of the first negative electrode active material to the second negative electrode active material is 4:6 to 6:

4.

15. The secondary battery according to any one of claims 1 to 14, characterized in that: The secondary battery meets one or more of the following conditions: The compaction density of the negative electrode film layer is 1.50 g / cc to 1.90 g / cc; The surface density of the negative electrode film layer is 6.0 mg / cm 2 ~24.0mg / cm 2 ; The thickness of the negative electrode film layer is 60 μm to 240 μm.

16. The secondary battery according to any one of claims 1 to 15, characterized in that: The porosity of the first region is greater than the porosity of the second region.

17. The secondary battery according to any one of claims 1 to 16, characterized in that: The method for preparing the first negative electrode active material comprises: Providing a base material; After mixing the base material and the organic carbon source, heat treatment is performed to obtain the first negative electrode active material; Wherein, the mass ratio of the matrix material to the organic carbon source is 100:1.5 to 100:

8.

18. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 17.

Citation Information

Patent Citations

  • Secondary battery and electric device

    CN116868395A

  • Negative electrode material, and negative electrode, electrochemical device, and electronic device using same

    CN118633180A

  • Security chip and clock gating method thereof

    KR1020250111475A

  • Negative electrode plate, secondary battery, battery pack, battery module, and electrical device

    US20230098119A1

  • Secondary battery, preparation method therefor, and battery module comprising same, and battery pack and device

    WO2022077370A1

Cited By

  • Battery monitoring method, device, system, equipment, medium and program product

    CN120778017A

  • Secondary battery and electric apparatus

    WO2026060957A1